Produção de peixes estéreis utilizando a hibridação e a manipulação cromossômica - Piva, Lucas Henrique [UNESP] (2016)
The use of sterile fish is a viable alternative avoid introgression in natural ecosystems. Additionally, sterile fish may be used as host in germ cell technologies for subsequent conservation of endangered species. Therefore, the present work aims to establish an efficient procedure for the mass production of sterile fish combining chromosome set manipulation and hybridization. Altiparanae astyanax oocytes were fertilized with sperm from A. fasciatus, A. schubarti, Hyphessobrycon anisitsi and Oligosarcus pintoi males, and half of the fertilized eggs was heat shocked at 40°C to induce triploidization. The intra-specific (pure) crossing triploid and diploid served as control. Fertilization and survival rates were observed in the developmental stages (cleavage, blastula, gastrula, somite and hatching), as well as the percentage of normal and abnormal larvae. The ploidy statuses of the larvae were confirmed by flow cytometry. At 9-months post fertilization, 16 males and 16 females from each cross were sacrificed for removal of the gonads and subsequent histological and sterility analysis. Additionally, fins samples were collected, fixed and diaphonized to verify the presence of sexual characteristics (bony hooks). There was no significant difference (P> 0.05) on the fertilization rate, survival of different embryonic stages, and percentage of normal larvae among all crossings and ploidies. Triploid females of A. altiparanae, diploid and triploid hybrid females of A. fasciatus, diploid hybrid females of Hyphessobrycon anisitsi and Oligosarcus pintoi, and triploid males of A. altiparanae and hybrid triploid A. fasciatus. were predominantly sterile. Females of all treatments showed no bony hooks in the anal fin, while such structures were observed in the anal fin of males, with the exception of hybrid triploid males of A. fasciatus. The results demonstrate that the hybridization associated with chromosome set manipulation showed to be an effective tool for mass sterilization of fish, with application in sustainable production and conservation of genetic resources.